The Profile of Galician-as-a-Foreign-Language Teachers: an eGrid-Based Approach - Blanco Favaro, Érika; Collazo Lugo, Teresa (Madrygal. Revista de Estudios Gallegos, 2024)
This article presents the results of an investigation whose aim is to describe the profile of teachers of Galician as a foreign language based on the eGrid self-assessment grid. The analysis carried out is based on quantitative and qualitative data collected through an online questionnaire that was distributed through emails and social networks. The results offer a first picture of the profile under study and confirm that teachers of this group, who perform their work in different countries around the world and various educational levels or teaching-learning contexts, are mostly female with a high knowledge of the Galician language and culture. The community is very divided between teachers who have more years of experience and those who are new. In addition, Galician studies have a limited presence compared to other subjects. The lack of visibility of the Galician language together with the geographical dispersion make the association of teachers necessary to create joint actions and offer teachers training.